Ordenamento e condução da produção em floresta ombrófila mista no estado do Rio Grande do Sul - Longhi, Régis Villanova (2016)
The aim was to plan the forest management in an Ombrophyllous Mixed Forest, based on volumetric growth parameters, initial density recovery time and commercial volume, obtained in an experimental management area, submitted to different intensities of selective cuts. The experimental management area is located in the municipality of Nova Prata and has a history of intense logging, presenting a highly modified forest structure and low frequency Araucaria angustifolia (Bertol.) Kuntze individuals. This forest has been monitored periodically at times of 4, 8 and 13 years after implementation of the intensities of selective cuts in 1.0 ha units, aiming to reduce angiosperm species of high absolute density. Cutting intensities are based on reduction of the frequency distribution curve adjusted in percentage levels compared to basal area in diameter classes, as follows: light selective cutting (20-30% reduction) and moderate selective cutting (40-50% reduction); and a control area (without management intervention), with a total sample area of 3.0 ha. In this area, the aim was to study the forest recovery after application of selective cuts. Recruitment and diameter growth of species of commercial value were evaluated in order to propose periodic cutting cycles for forest conversion to a production structure in the future. The level of reduction in population density that showed the best results was taken as the basis for the study of frequency projections in diameter classes after selective logging using the Transition Matrix and Ratio Movement in diametric amplitude of 5 cm and 10 cm. Projected and observed frequencies were compared by Kolmogorov-Smirnov (K-S) test. After determining the most accurate projection of frequency in diameter classes, regulation of yield was carried out to an araucaria forest, located in the municipality of Boqueirão do Leão, RS. The results allowed inferring that the reduced levels of high density angiosperms species in the araucaria forest of Nova Prata, RS, provided an increase in species diversity indexes, increasing the recruitment of commercial individual species, especially regarding the Araucaria angustifolia, with growth rates higher than in the control area. In addition, periodic interventions at intervals of 10 years with reduction of 20-30% of the total basal area per DBH class, proved to be more effective for the transformation of the forest to a production structure in the future. According to this recommended level of intensity, the ratio movement method, with diameter range of 10 cm, showed greater accuracy to predict the frequencies in diameter classes after selective logging. With these experimental parameters, to the araucaria forest of Boqueirão do Leão, RS, were simulated three management alternatives that consisted of cutting the trees above the required maximum diameter of 60 cm and introduction of percentage reductions in levels adjusted frequency. The Araucaria angustifolia has 38% of the basal area and 52% of the commercial volume of the forest, with a density of 150 ind.ha-1, demonstrating the high potential of production. The management alternatives indicated a period of 10 to 15 years to recover the original timber stock. The projection of the frequency distribution in diameter class for each management alternative also indicated that the forest can recover density and initial commercial volume for the given cutting cycle, but need more time to recover in the last diameter class (DBH > 70 cm). Management proposals allow the sustainable use of the araucaria forest, adding economic value by providing an alternative use by landowners.